2021
DOI: 10.3390/microorganisms10010059
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at the Contribution of Oral Microbiota to the Pathogenesis of Rheumatoid Arthritis: A Narrative Review

Abstract: Although autoimmunity contributes to rheumatoid arthritis (RA), several lines of evidence challenge the dogma that it is mainly an autoimmune disorder. As RA-associated human leukocyte antigens shape microbiomes and increase the risk of dysbiosis in mucosae, RA might rather be induced by epigenetic changes in long-lived synovial presenting cells, stressed by excessive translocations into joints of bacteria from the poorly cultivable gut, lung, or oral microbiota (in the same way as more pathogenic bacteria can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 94 publications
0
17
0
2
Order By: Relevance
“…The gut microbiome has increasingly emerged as a critical player in the onset and progression of RA 24. Notably, studies have revealed that changes in the gut microbiota composition are involved in the pathophysiology of RA 8 25 26.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome has increasingly emerged as a critical player in the onset and progression of RA 24. Notably, studies have revealed that changes in the gut microbiota composition are involved in the pathophysiology of RA 8 25 26.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither P. gingivalis nor A. actinomycetemcomitans was related to the alveolar bone loss or severity of arthritis in a mouse model [ 7 ]. It is suggested that persistent bacterial translocations from the oral cavity to the gut would increase intestinal permeability, resulting in penetration of oral bacteria into blood, triggering synovial autoimmunity in RA [ 8 ]. However, P. gingivalis might hardly survive the trip to the gut in humans [ 9 ] although it could translocate from a gingival site to stool in a mouse model of arthritis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, P. gingivalis might hardly survive the trip to the gut in humans [ 9 ] although it could translocate from a gingival site to stool in a mouse model of arthritis [ 10 ]. Therefore, it was proposed that other oral microbes might be associated with the pathogenesis and progression of RA [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contribution of the oral microbiota to the etiopathogenesis of RA was recently discussed by Berthelot et al [ 13 ]. They stated that a growing body of evidence supports that oral bacteria, such as Porphyromonas gingivalis , contribute to the pathogenesis of RA, although the genetic background of patients may also play a role [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contribution of the oral microbiota to the etiopathogenesis of RA was recently discussed by Berthelot et al [ 13 ]. They stated that a growing body of evidence supports that oral bacteria, such as Porphyromonas gingivalis , contribute to the pathogenesis of RA, although the genetic background of patients may also play a role [ 13 ]. Studies relying on the high-throughput sequencing 16S ribosomal DNA gene ampliconspointed to Prevotella as a periodontal taxa of interest among the oral microbiota of patients with RA [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%